Implementation of Combined Blasting at Oyu Tolgoi - Chris Batten; Bayu Saputra; Bilegt Batbold (International Society of Explosives Engineers, 2025)
The ability to fire multiple blasts simultaneously can provide significant benefits to any open pit mining operation. Reduced blast-related downtime by reducing blast events can increase equipment utilization and maximize material movement. Significant sequencing benefits can also be delivered, associated with reduced equipment relocation. This paper describes the work completed in partnership between Orica and Oyu Tolgoi to successfully demonstrate that combined production-trim and midsplit blasting could be implemented successfully while successfully managing the risk of increased damage to the final walls. The paper details the methodology used to assess key performance measures linked to final wall damage and compares the performance between the following blasting methods. • Free face trim blasting vs. combined production-trim blasting • Presplit blasting vs. midsplit blasting. The results of the initial trial blasts are presented, along with the method agreed by the key site stakeholders for ongoing application. The method used to keep the risk of final wall damage to an acceptable level is explained, along with the benefits delivered to Oyu Tolgoi operations associated with the initial 12 months of application.